A High Plane of Nutrition Is Associated with a Lower Risk for Neonatal Calf Diarrhea on Bavarian Dairy Farms - Ingrid Lorenz; Regina Huber; Florian M. Trefz (Animals, 2021)
In all bovine production systems, neonatal calf diarrhea remains worldwide an important issue of economic losses and animal welfare. The aim of the present study was to identify risk factors for neonatal calf diarrhea as a herd health problem on Bavarian dairy farms. For the purpose of this study, management factors related to calf health were retrospectively compared between 59 dairy farms with calf diarrhea as a herd problem with those of 18 control farms, where no veterinary treatment of calves for neonatal calf diarrhea took place for at least one year prior to the farm visit. A multivariable binary logistic regression analysis of management factors indicated that administration of 3 L or more of colostrum at the second feeding after birth (Odds ration [OR] = 0.21, 95% confidence interval [95% CI] = 0.05–0.89), ad libitum feeding of milk during the first week of life (OR = 0.06, 95% CI = 0.006–0.60), and administration of an iron containing preparation after birth (OR = 10.9, 95% CI = 1.25–95.6) were independently associated with the presence of a herd problem with neonatal diarrhea. Results of this study therefore suggest that a higher plane of nutrition is a protective factor with regard to the occurrence of neonatal diarrhea on Bavarian dairy farms. These findings support the establishment of ad libitum feeding programs in dairy calf rearing.